2021
DOI: 10.1101/2021.06.10.447903
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meditation-induced effects on whole-brain structural and effective connectivity

Abstract: In the past decades, there has been a growing scientific interest in characterizing neural correlates of meditation training. Nonetheless, the mechanisms underlying meditation remain elusive. In the present work, we investigated meditation-related changes in structural and functional connectivities (SC and FC, respectively). For this purpose, we scanned experienced meditators and control (naive) subjects using magnetic resonance imaging (MRI) to acquire structural and functional data during two conditions, res… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 78 publications
(22 reference statements)
2
2
0
Order By: Relevance
“…We also found that changes in regions in visual- and default-mode- networks indexed differences between deep sleep and wakeful resting, consistent with other studies of the human wake-sleep cycle 67 69 . In contrast, comparing meditation with resting state in expert meditators revealed regions in limbic- and default-mode- networks, similar to other findings in meditation 70 74 .…”
Section: Discussionsupporting
confidence: 85%
“…We also found that changes in regions in visual- and default-mode- networks indexed differences between deep sleep and wakeful resting, consistent with other studies of the human wake-sleep cycle 67 69 . In contrast, comparing meditation with resting state in expert meditators revealed regions in limbic- and default-mode- networks, similar to other findings in meditation 70 74 .…”
Section: Discussionsupporting
confidence: 85%
“…We also found that changes in regions in visual-and default-mode-networks indexed differences between deep sleep and wakeful resting, consistent with other studies of the human wake-sleep cycle (Horovitz et al, 2009;Ipiña et al, 2020;Stevner et al, 2019). In contrast, comparing meditation with resting state in expert meditators revealed regions in limbic-and default-mode-networks, similar to other findings in meditation (Filippi et al, 2021;Tang et al, 2015;Taylor et al, 2013).…”
Section: Fine-grained Node-level Turbulence Differences Between Brain Statessupporting
confidence: 91%
“…For the whole-brain model, we used an average structural connectivity matrix (SC) from a sample of 38 unrelated healthy subjects previously described in De Filippi et al (2021). MRI images were acquired on a 3T whole-body Siemens TRIO scanner (Hospital Clínic, Barcelona) using a dual spin-echo difussion tensor imaging (DTI) sequence (TR = 680ms; TE = 92ms; FOV = 236mm; 60 contiguous axial slices; isotropic voxel size 2 × 2 × 2 mm; no gap, and 118 × 118 matrix sizes).…”
Section: Difussion Tensor Imaging Acquisition and Preprocessingmentioning
confidence: 99%